PENGARUH PENAMBAHAN BIOCHAR LIMBAH PERTANIAN DAN PESTISIDA PADA INKUBASI TANAH INCEPTISOL UNTUK MENEKAN EMISI GAS METANA (CH4) SEBAGAI GAS RUMAH KACA - Winda Prihantarawati Cahayaningtyas; Indro Sumantri (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Methane (CH4) is one of the gases that cause global warming, which ranks second only to carbon dioxide (CO2).Naturally, peat lands, wetlands, and sediments in coastal areas are major source of methane gas in the atmosphere (Hardy, 2003). The use of biochar as a companion or replacement for pesticides in agricultural system can increase crop productivity and reduce the emission of methane (CH4) significantly. The research method used is an incubation inceptisol soil. Variables that were varied were the addition of agricultural waste biochar (without biochar, rice husks biochar and corn cobs biochar) and the addition of several types of pesticides like organophosphate insecticides, carbamate insecticides, pyrethroid insecticides, paraquat herbicides and bio-insecticides. The analysis of methane emissions by Gas Chromatography (GC), analysis of degree acidity (pH) using pH-meter and analysis of the number of bacteria at the end of the incubation period using Standard Plate Count (SPC). In the analysis of total methane emissions, the addition of rice husk biochar and without the addition of pesticides (P0B1) to the treatment, produced the largest emissions of methane (CH4) to 4.494 mg CH4/g soil (increase 348.7% ), and the treatment given to the addition of pyrethroid insecticides and rice husk biochar (P3B1) produced the lowest emissions at 0.011 mg CH4/g soil (reduce 98.9%). This incubation process takes place in the pH range 5.2 to 6.7. The population of bacteria in the end incubation, P3B2 treatment (addition of pyrethroid pesticides and biochar corn cobs) has largest population of bacteria which is equal to 4.2 x 108 the bacteria/mL, whereas the P2B1 treatment (addition of carbamate pesticides and rice husk biochar) has lowest population of bacteria about 3.5 x 106 bacteria / mL.